Survey of Prevalence of Hepatitis G in Blood Donors Admitted to Yazd Blood Transfusion Center (2012) - A Astani; F Akhavan Tafti; A Emami; M Izadi; G Eslami; M Vakili (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2017)
Introduction: Hepatitis G virus is an RNA virus related to Flaviviridae family that its genome was identified in the patients with non A-E hepatitis at the end of the last century. The present study aimed to investigate the survey of the prevalence of hepatitis G in blood donors and its relation to age and gender Methods: In this descriptive cross-sectional study, sampling was performed on 263 blood donors referring to Yazd Blood Transfusion Center. RNA extraction and cDNA synthesis was performed according to the protocol  and  was amplified by nested-PCR. Finding: Out of 263 examined donors, 12.9% were first time donors, 20.9% and 66.2%% were repeated and regular donors. More donors were in the range of 30-40 years (33.5%), 98.9% (260) were men and 1/1% (3) female. Only in 3 (1.1%) of donors, HGV genome were identified, which all cases were related to male in the age of 22-32 years old. 2 (7/0%) of HGV positive donors were regular donors and one of the donors has been reported as a repeated donor.  No genomic HGV was reported in first time donors in this study. Conclusion: According to the various studies in Iran, infection with HGV genome was reported from 4% in blood donors to 32% in hemodialysis patients. Therefore, it seemsthat it is necessary to do more studies in the country to evaluate blood donors.